Beszélhetünk-e Jézus pubertás- és kamaszkoráról? – A szülők és gyermekük közötti konfliktus feloldása a megbékélés és az egészséges személyiségfejlődés céljából a 12 éves Jézus története alapján a Lk 2,41–52 szerint – - Gyöngyi HERDEAN (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
Can we talk about the puberty and adolescence of Jesus? – Conflict resolution between parents and their child with the purpose of reconciliation and healthy personality development based on the story of the 12-year-old Jesus according to Luke 2:41-52 −